ACTIVITY ETHANOL EXTRACT, ETHYLE ACETATE FRACTION, N-HEXAN FRACTION OF SOFO-SOFO LEAVES (Acmella cf) Against Propionibacterium acnes AND Staphylococcus epidermidis AS ANTIBACTERIES - Eva Diansari Marbun; Alfi Sapitri; Vivi Asfianti (Universitas Negeri Medan, 2021)
Sofo-sofo leaves are traditional medicinal plants that have been known by the Nias people to cure fever, coughs, diarrhea and antimicrobial infections on the skin surface. The purpose of this study was to determine the antibacterial activity of ethanol extract, n-hexane fraction and ethylacetate fraction Sofo-sofo leaf (Acmella cf) against Propionibacterium acnes and Staphylococcus epidermidis. Simplicia powder was characterized and phytochemical screening was performed. Furthermore, it was isolated using 96% ethanol solvent and fractionated with n-hexane and ethylacetate to obtain extracts. Then test the antibacterial activity of each extract against Propionibacterium acne and Staphylococcus epidermidis by using a diffusion method disc paper. The research results obtained water content 5.66%, water soluble extract content 27.33%, ethanol soluble extract content 13.61%, total ash content 14.39%, and acid insoluble ash content 6.25%. The highest antibacterial activity was given by ethylacetate extract at a concentration of 2% (23.4 ± 0.2) compared to ethanol extract with a concentration of 2% (21.06 ± 0.85) and 2% concentrated n-hexane extract (19.36 ± 0.16) against the Propionibacterium acne bacteria. The highest antibacterial activity was ethyl acetate extract at a concentration of 2% (23.24 ± 0.23), ethanol extract with a concentration of 2% (16.36 ± 1.76) and n-hexane extract at a concentration of 2% (15.36 ± 0 , 11) against Staphylococcus epidermidis bacteria. The antibacterial activity results were analyzed by the one way ANOVA test method. Based on these results it can be concluded that there are differences between treatment groups, which is indicated by a significant value <0.05.